Tangier and the cultivation of desire in the print travel guides: latent and transgressive forms - Anas Sanoussi (Via@)
This article examines the different ways in which the city of Tangier is presented as a site of erotic experiences in the three large collections of print travel guides (Guide Vert, Guide Bleu and Lonely Planet) published in France after Moroccan independence (1956-2010). Heteroeroticism, which was deemed appropriate in the West’s promotional discourse on destinations with a colonial culture, no longer responds to the demands of a hypermodern touristic public in search of a more reflexive and creative experience. The figure of the artist passing through Tangier emerges as a central aspect of the touristic discourse in the contemporary travel guides, serving as a viaticum to the reader. In particular, the Lonely Planet, whose discourse championed homoeroticism from its very earliest French editions, allows us to understand the modalities of the cultivation of desire in relation to certain components of the touristic imagination of Tangier.